The impact of the recent expansion of the EU on the UK labour market - David G. Blanchflower; Helen Lawton (Institute for the Study of Labor (IZA), 2008)
We examine the impact on the UK of the influx of workers from Eastern Europe. We look at the characteristics of the workers who have come to the UK since 2004. We also use data from a number of Eurobarometers 2004-2007 as well as the 2005 Work Orientation module International Social Survey Programme to look at the attitudes of residents of these countries. East Europeans report that they are unhappy with their lives and the country they live in, are dissatisfied with their jobs and would find difficulties in finding a new job or keeping their existing job. Relatively high proportions express a desire to move abroad. Expectations for the future for both their economy and their personal situations remain low but have improved since 2004. There has been some deterioration in the availability of jobs in the UK economy as the economy moves into recession. The UK is an attractive place to live and work for these workers. We argue that rather than dissipate, flows to the UK could remain strong well into the future.
urn:nbn:de:101:1-2008101410
Keywords: J61; 330; EU expansion; migration; attitudes; Internationale Arbeitsmobilität; Ausländische Arbeitskräfte; Osteuropäer; Arbeitsmarkt; Meinung; Großbritannien; EU-Erweiterung; EU-Staaten (Osteuropa)